Asymmetric Dieckmann Condensation towards Spirocyclic Oxindoles Catalyzed by Amino Acid‐Derived Phosphonium Salts. Issue 2 (16th November 2021) - Yu, Longhui; Liu, Jun; Wang, Hongyu; Xu, Lijun; Wu, Yufei; Zheng, Changwu; Zhao, Gang
Abstract: An asymmetric Dieckmann condensation towards spirocyclic oxindoles and aza‐oxindoles catalyzed by amino acid‐derived phosphonium salt has been developed, which expanded the applicability of asymmetric phosphonium salt catalysis in the production of 1, 3‐dicarbonyl compounds. This reaction is distinguished by its mild conditions (−20 °C), low catalyst loading (3–5 mol%), and broad substrate scope (25 examples). Control experiments revealed that both the catalyst's phosphonium skeleton and H‐bonding site were required. Product transformations and a gram scale experiment were also carried out. Abstract :